Safety of Acheta domesticus powder as a Novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Alexandre Maciuk; Inge Mangelsdorf; Harry J. McArdle; Androniki Naska; Kristina Pentieva; Alfonso Siani; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on Acheta (A.) domesticus powder as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The main components of the NF are protein, fat and dietary fibre (chitin). The Panel notes that the concentration of contaminants in the NF depends on the occurrence levels of these substances in the insect feed. The Panel further notes that there are no safety concerns regarding the stability of the NF if the NF complies with the proposed specification limits during its entire shelf‐life. The NF has a high protein content, although the true protein content is overestimated when using the nitrogen‐to‐protein conversion factor of 6.25 due to the presence of non‐protein nitrogen from chitin. The applicant proposed to use the NF as food ingredient in a number of food products. The target population proposed by the applicant is the general population. Considering the composition of the NF and the proposed conditions of use, the consumption of the NF is not nutritionally disadvantageous. The panel notes that no safety concerns arise from the toxicological information of A. domesticus. The panel considers that the consumption of the NF might trigger primary sensitisation to A. domesticus proteins and may cause allergic reactions in subjects allergic to crustaceans, mites and molluscs. Additionally, allergens from the feed may end up in the NF. The panel concludes that the NF is safe under the proposed uses and use levels.